Turbulent Channel Flow Simulation Using LES Dynamic Model (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Turbulent flow modelling has increasingly becomeone of the main scientific research occupations, seeking todevelop a universal modelling approach that can describeaccurately the dynamics of all turbulent flow scales. Modernattempts try to bring together two main objectives; theapplicability of the turbulent flow models to complex flowconfigurations of industrial interest as well as reducing thecomputational costs needed for their resolution. Large EddySimulation (LES) modelling approach has many promisingfeatures among all other turbulent flow modellingapproaches such as RANS or DNS. In this study, LESmodelling approach has been demonstrated and applied toturbulent channel flow at moderate Reynolds number using Fluent solver. The obtained turbulent flowstatistics were compared to their corresponding values of a detailed, well resolved DNS simulation. The obtained LESturbulent flow statistics have an acceptable trend to those ofthe reference DNS results, which reflects the validity of theLES approach to model turbulent flows accurately andencourages its use in predicting turbulent motion forindustrial and engineering applications.